Optimasi Konsentrasi Media Pendingin Soluble Oil dan Feedrate terhadap Kekasaran Permukaan pada Proses Permesinan Milling Vertikal Baja ST37 - Rafi Afifuddin A; Nicky Suwandhy Widhi Supriyanto (Jurnal Kendali Teknik dan Sains, 2025)
In the manufacturing industry, surface roughness is one of the important quality parameters in machining results, especially in the vertical milling process. This study aims to optimize the concentration of soluble oil coolant and feed rate on the surface roughness of ST 37 steel using the Taguchi method. The material used is ST 37 steel with dimensions of 10 mm × 17 mm × 50 mm, processed using a Dixon XZ7550CW vertical milling machine with a 10 mm diameter HSS endmill. Variations in the concentration of Randocut 500 coolant (3%, 5%, 10%) and feed rate (24, 40, 65 mm/min) were tested with fixed parameters such as a depth of cut of 0.5 mm and a spindle speed of 580 rpm. Surface roughness values (Ra) were measured using a surface roughness tester and analyzed using the Taguchi method and ANOVA. The results showed that a coolant concentration of 5% and a feedrate of 24 mm/min produced the lowest surface roughness (2.24 µm) with the highest S/N ratio (-7.01 dB). ANOVA analysis revealed that feed rate had the most dominant influence (62.4%) on surface roughness, followed by coolant concentration (36.8%). The optimal combination to minimize surface roughness is a concentration of 5% and a feed rate of 24 mm/min..